Bringing Sisters Back Together Another Look at Luke 10:41-42 - Wasserman, Tommy 1970- (2018)
Luke's account of Martha and Mary of Bethany is present in the textual tradition in two versions. The majority of scholars and editors prefer the shorter reading, "only one thing is necessary." This view is also taken up by the influential UBS Committee, which regards the long reading as a conflation. This preference for the shorter reading is mistaken on several grounds. First, it builds on a factual error presupposing a reading that does not exist in the extant Greek textual tradition. Second, it neglects the history of interpretation and specifically its significance for the textual problem. Third, it is motivated at least in part by positing a dichotomy between the two sisters. In this article, I argue that the long reading in the passage in Luke 10:41-42, where Jesus replies to Martha that "few things are necessary, or indeed only one" is the initial text and the lectio difficilior, as well as the text that is best suited to its narrative context in Luke's Gospel.
Keywords: Bible. Gospels; Bible. Luke; Jesus Christ; MARTHA, Saint; Mary, Blessed Virgin, Saint